2020
DOI: 10.1038/s41467-020-18181-6
|View full text |Cite|
|
Sign up to set email alerts
|

Fast and multiplexed superresolution imaging with DNA-PAINT-ERS

Abstract: DNA points accumulation for imaging in nanoscale topography (DNA-PAINT) facilitates multiplexing in superresolution microscopy but is practically limited by slow imaging speed. To address this issue, we propose the additions of ethylene carbonate (EC) to the imaging buffer, sequence repeats to the docking strand, and a spacer between the docking strand and the affinity agent. Collectively termed DNA-PAINT-ERS (E = EC, R = Repeating sequence, and S = Spacer), these strategies can be easily integrated into curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 24 publications
(39 reference statements)
3
76
0
Order By: Relevance
“…When the DNA length is over 12 bp, the excimer emission decreased. According to previous results from the DNA‐PAINT technique, imager strands with lengths ranging from 8 to 12 bp exhibit a metastable hybridization state [13] . Here, we measured the binding constants between K21 and dsDNAs with lengths ranging from 4 bp to 30 bp (Supporting Information, Figure S5 and Table S2).…”
Section: Resultsmentioning
confidence: 80%
“…When the DNA length is over 12 bp, the excimer emission decreased. According to previous results from the DNA‐PAINT technique, imager strands with lengths ranging from 8 to 12 bp exhibit a metastable hybridization state [13] . Here, we measured the binding constants between K21 and dsDNAs with lengths ranging from 4 bp to 30 bp (Supporting Information, Figure S5 and Table S2).…”
Section: Resultsmentioning
confidence: 80%
“…Another way to affect hybridisation kinetics is by introducing ethylene carbonate (EC) an aprotic solvent thought to increase the solubility of the DNA bases [68]. Studied at the single-molecule level, in the presence of 0-15% EC, there is a five to tenfold decrease in k off in the transient binding of a 9-nucleotide probe.…”
Section: Ethylene Carbonatementioning
confidence: 99%
“…According to previous results from the DNA-PAINT technique,i mager strands with lengths ranging from 8t o1 2bp exhibit am etastable hybridization state. [13] Here,w em easured the binding constants between K21 and dsDNAs with lengths ranging from 4bpt o3 0bp( Supporting Information, Figure S5 and Table S2). We found that compared to the shorter (4 bp) or longer (30 bp) ones,the dsDNAs of 7-12 bp show intermediate affinities towards K21, which further support the idea about DNAm etastable hybridization state Figure 3.…”
Section: Resultsmentioning
confidence: 99%